Effective removal of Fluoride ions by rGO/ZrO2 nanocomposite from aqueous solution: Fixed bed column adsorption modelling and its adsorption mechanism - Mohan S.; Singh D.K.; Kumar V.; Hasan S.H. (My University, 2025)
A continuous fixed-bed column study was performed using rGO/ZrO2 as an excellent adsorbent for the removal of F-from water. The column experiments were performed at laboratory scale to examine the potentiality of rGO/ZrO2 at various initial F-concentration, bed height, and flow rate. The rGO/ZrO2 nanocomposite was proved to be very promising adsorbent as it showed the excellent adsorption capacity for F-. The maximum adsorption capacity of the rGO/ZrO2 was found to be 45.7 mg/g at an initial F-concentration of 25 mg/L, bed height of 7.5 cm, a flow rate of 1.66 mL/min at pH 7. The Thomas, BDST, and Yoon–Nelson models were applied to the experimental data to predict the breakthrough curves. Although both the Thomas and Yoon–Nelson models showed good agreement with the experimental data but the Yoon–Nelson model was found to provide the best representation for F-adsorption on the adsorbent. Moreover, the exhausted column was regenerated with 10% NaOH solution successfully with a slight decrease in column capacity up to three adsorption-desorption cycles. Life factor calculation revealed that the nanoadsorbent bed would have sufficient capacity to avoid breakthrough at time t = 0 up to 15.11 cycles. © 2016 Elsevier B.V.